Analysis of Parental Involvement in Achieving Sustainable Development Goals (SDGs) 4 - Nor-Hayna Dasad Tadol; Chuti Neem; Gifa Oktavia; Afifah Febriani (International Islamic Studies Development and Research Center (IISDRC), 2025)
Parental involvement in children's education is key to determining children's readiness for education and supporting their academic success. This study aims to analyze the forms of parental involvement in achieving Sustainable Development Goals (SDGs) 4. This study uses a qualitative method with a case study approach. The data sources were obtained from in-depth interviews with ten informants consisting of parents. All interview results were analyzed using Milles Huberman. Based on the results of the data analysis, the author found seven research results related to parental involvement in achieving Sustainable Development Goals (SDGs) 4. The seven research findings are: i) establishing closeness with children, ii) providing learning facilities for children, iii) monitoring children's development, iv) managing study schedules, v) collaborating with teachers, vi) supervising and assisting children's learning activities, and vii) providing rewards. These seven forms of parental involvement in children's education can be used as a reference for all parents in welcoming a bright future for their children in order to achieve Sustainable Development Goals (SDGs) 4 namely quality education in Indonesia.